Nghiên cứu về lợi ích kế toán trong môi trường hệ thống hoạch định nguồn lực doanh nghiệp - Võ Văn Nhị; Phạm Trà Lam (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2017)
In the past decade organisations all over the world have adopted enterprise resource planning (ERP) systems. In this context, the aim of this study is to investigate the accounting benefits as perceived by accountants. The results provide additional bases for assessing the success of ERP system to researchers, businesses, and suppliers. The data are retrieved from 114 individuals. The results of the EFA analysis reveal that respondents have quoted a number of benefits they derived from ERP systems in the accounting process. There are five dimensions to the accounting benefits including: (i) accounting tasks performance benefits; (ii) IT accounting benefits; (iii) organisational accounting benefits; (iv) financial management benefits; and (v) managerial accounting benefits.